Geography of loneliness: the politics of deterritorialisation in the aprtheid writings of Nadine Gordimer and J.M. Coetzee - Pan-IAm, Morakot (2021)
This thesis explores Nadine Gordimer’s and J. M. Coetzee’s political consciousness as it is represented in the narrative embodiment of the separation-based condition of politicised loneliness, and as it is recognised and established in the representation of and investment in the counter politics of deterritorialisation. My research looks to the theoretical frameworks of Hannah Arendt’s understanding of loneliness to devise an alternative way of thinking about and looking at the problems of apartheid in terms of political spatiality, and Gilles Deleuze and Felix Guattari’s concept of deterritorialisation to construct new approaches to the political and spatial impasse set up by the apartheid regime. Interchangeably, these two theoretical frameworks allow for wider possibilities of understanding about the spatiality of politics in apartheid South Africa.